Modulating FOXO3 transcriptional activity by small, DBD-binding molecules - Hagenbuchner, Judith; Obsilova, Veronika; Kaserer, Teresa; Kaiser, Nora; Rass, Bettina; Psenakova, Katarina; Docekal, Vojtech; Alblová, Miroslava; Kohoutova, Klara; Schuster, Daniela; Aneichyk, Tatsiana; Vesely, Jan; et al. (eLife, 2019)
FOXO transcription factors are critical regulators of cell homeostasis and steer cell death, differentiation and longevity in mammalian cells. By combined pharmacophore-modeling-based in silico and fluorescence polarization-based screening we identified small molecules that physically interact with the DNA-binding domain (DBD) of FOXO3 and modulate the FOXO3 transcriptional program in human cells. The mode of interaction between compounds and the FOXO3-DBD was assessed via NMR spectroscopy and docking studies. We demonstrate that compounds S9 and its oxalate salt S9OX interfere with FOXO3 target promoter binding, gene transcription and modulate the physiologic program activated by FOXO3 in cancer cells. These small molecules prove the druggability of the FOXO-DBD and provide a structural basis for modulating these important homeostasis regulators in normal and malignant cells.
Keywords: DNA; promotorové oblasti (genetika); Gene Expression Profiling; Nucleic Acid Conformation; vazba proteinů; Models, Molecular; protein FOXO3; vazebná místa; lidé; HEK293 buňky; Forkhead Box Protein O3; Protein Domains; Small Molecule Libraries; Transcription, Genetic; simulace molekulového dockingu; Protein Binding; genetická transkripce; Gene Knockdown Techniques; HEK293 Cells; molekulární modely; magnetická rezonanční spektroskopie; Humans; knihovny malých molekul; Promoter Regions, Genetic; nádorové buněčné linie; Binding Sites; proteinové domény; Molecular Docking Simulation; genový knockdown; stanovení celkové genové exprese; konformace nukleové kyseliny; Cell Line, Tumor; Magnetic Resonance Spectroscopy